ANALYSIS OF RISK FACTORS, BEHAVIOR, AND ENVIRONMENTAL CONDITIONS FOR LEPTOSPIROSIS DISEASE IN PEMATANG PASIR VILLAGE, TELUK NIBUNG DISTRICT, TANJUNG BALAI CITY - Safira, Putri; Nanda, Meutia; Salsabilla, Salsabilla; Elvina, Elvina; Angraini, Riri; Sianturi, Anggina Cucu Khetri; Putri, Dian Yustika (HEARTY, 2025)
Leptospirosis is a zoonotic disease that is transmitted through contact with the urine of infected animals, especially rats, and often occurs in environments with poor sanitation. This study aims to analyze behavioral risk factors and environmental conditions that contribute to the spread of leptospirosis in Pematang Pasir Village, Teluk Nibung District, Tanjung Balai City in 2024. The study used a cross-sectional design involving 50 respondents aged 17 years and older from Wards I and VI. Data were collected through interviews using questionnaires that assessed respondents' knowledge, attitudes, and actions related to leptospirosis, as well as direct observation of environmental conditions such as waterlogging, the presence of rats, and sanitary conditions. The results showed that the majority of respondents (88%) had low knowledge about leptospirosis, although 80% implemented good personal hygiene behaviors. Only 18% of respondents carried out adequate rat control measures. Environmental observations revealed that 96% of respondents experienced puddles around their homes, and 100% indicated that their neighborhoods were flooded frequently. The presence of garbage around the house was found in 98% of respondents, and 98% of respondents often saw rats in or around the house. Most respondents (90%) had a house ≥ 2 meters away from the sewer, with 92% reporting good road conditions. Only 24% of respondents have pets, and 4% live close to ponds (< 700 meters). Factors such as poor sanitation, the presence of rodents, and the high risk of flooding are the main factors that affect the risk of spreading leptospirosis in the region. This study emphasizes the importance of increasing public education about leptospirosis and its prevention measures, as well as environmental improvement efforts to reduce the risk of infection in the affected areas.